Systematic Literature Review on The Hierarchical Linear Model Method in Analyzing Capital Structure Policies Across Various Industrial Sectors - Silvana Syah; Obing Zaid Sobir; Agung Dharmawan Buchdadi; Ruswiati Suryasaputra (IJHCM (International Journal of Human Capital Management), 2023)
This study aims to understand the contributions, findings, and recent developments in the application of the HLM method in this context, as well as to identify existing knowledge gaps. This systematic literature review investigates the application of the Hierarchical Linear Model (HLM) method in the analysis of capital structure policies across various industrial sectors, focusing on studies conducted between 2017 and 2022. The review encompasses four primary research contributions, each providing unique insights into the intricate determinants of capital structure decisions. In conclusion, the HLM method emerges as a robust tool for understanding the contextual and dynamic factors shaping capital structure decisions, and the review underscores the importance of industry-specific nuances and regional disparities in this realm.